Sicca syndrome in the same family – the importance of anti-Ro60, anti-Ro52 and anti-La antibody profiling in Sjögren’s syndrome - Arkadiusz Koszarny (Termedia Publishing House, 2021)
Sicca syndrome, which is typical for Sjögren’s syndrome (SS), is relatively often comorbid with other autoimmune diseases. The current classification criteria for SS published in 2016 include only anti-SSA (anti-Ro) autoantibody, while the latest literature proposes that anti-Ro60/anti-Ro52 autoantibody profiles should be used instead, as these two types of antibodies correlate with specific clinical symptoms and laboratory test findings. The paper presents the case of a 41-year-old woman suffering from primary Sjögren’s syndrome (pSS) and her three daughters, who were under observation for rheumatic disorders due to sicca symptoms, especially pSS, as well as a discussion on separate determination of anti-Ro60 and anti-Ro52 autoantibodies based on current literature in the PubMed database. When testing with antinuclear antibodies, the Ro60+Ro52+La+ autoantibody profile most closely matches for pSS. Further research is needed to find marker antibodies for SS and quantification methods.